Analysis of differentially expressed genes in hypertension and hypertensive cerebral hemorrhage via RNA-sequencing - Hongwu Qi; Min Qiao; Yansong Liu; Weijun Zeng; Lizhao Zhang; Hongjun Guo (All Life)
Hypertension (HT) is a major cause of intracerebral hemorrhage (ICH), and hypertensive cerebral hemorrhage (HCH) has a serious impact on life quality of patients and gives society a heavy burden. This study investigated the key genes involved in HT and HCH. Three patients with HT, three with HCH, and three healthy individuals were recruited in the present study. Shared and specific differentially expressed genes (DEGs) in HT and HCH were identified using RNA sequencing and bioinformatics analysis. Functional annotation and protein–protein interaction (PPI) network construction of HT- and HCH-specific DEGs were conducted. Estimation of cell infiltration, drug prediction, and real-time qPCR (RT-qPCR) validation were performed. Compared with the controls, 502 and 1649 DEGs were identified in the HT and HCH groups, respectively. Among them, 378 DEGs were HT-specific and 633 DEGs were HCH-specific, and a total of 1771 DEGs were identified between HT and HCH. In addition, there were fewer immune cell types that differed significantly among the three groups. The RT-qPCR validation results in human subjects and cell models were generally consistent with the sequencing results. Our study may make a contribution for the understanding of the specific mechanisms of HT and HCH. Highlights Hypertension (HT) is a major cause of intracerebral hemorrhage (ICH), and hypertensive cerebral hemorrhage (HCH) has a serious impact on life quality of patients. A total of 502 and 1649 DEGs were obtained in HT and HCH, and 1771 DEGs were obtained between HT and HCH. Doxycycline, fasudil and propylthiouracil were predicted as potential drugs for HT and HCH. Our study may make a contribution for the understanding of the specific mechanisms of HT and HCH and representing a potential novel strategy for HT and HCH treatment.